Blue Economy Sebagai Solusi Keluar Dari Middle Income Trap - Ayuningtyas, Agian Dila; Muchlisoh, Siti (Politeknik Statistika STIS, 2024)
From 2001 to 2021, the income slowdown in Indonesia has led to the middle-income trap phenomenon. Indonesia has significant potential in the blue economy sector due to its vast marine area of 6,4 million square kilometers, 1,8 million hectares of seagrass beds, and 3,4 million hectares of mangroves. This potential can be leveraged by Indonesia as an alternative solution to the middle-income trap issue. This study uses World Bank and World Tourism Data from 2001-2021. A multiple linear regression model is employed to determine the impact of blue economy variables on Indonesia's national per capita income. The results show that blue economy variables such as aquaculture production and total sea containers positively impact. Conversely, capture fisheries production and marine tourism negatively impact, while the percentage of protected areas has no significant effect on Indonesia's national per capita income. Policy simulation results indicate that increasing capture fisheries and aquaculture production can be a solution to overcome the middle-income trap.